2012
DOI: 10.1159/000345371
|View full text |Cite
|
Sign up to set email alerts
|

Self-Rated Anosognosia Score May Be a Sensitive and Predictive Indicator for Progressive Brain Atrophy in Amyotrophic Lateral Sclerosis: An X-Ray Computed Tomographic Study

Abstract: We investigated whether a self-rated anosognosia score can be an indicator for progression of brain atrophy in patients with amyotrophic lateral sclerosis (ALS). Scores for 16 patients were compared with the ventricular areas of the bilateral anterior and inferior horns measured on x-ray computed tomography. Longitudinal enlargement was expressed as a monthly increase in size: (ventricular size at the initial scan – ventricular size at the follow-up scan)/scan interval (months). The anosognosia scores ranged f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…(2006)Ordinal regression; F and Bonferroni tests p < 0.005Not applicable (visual inspection) p < 0.001Loss of insight into behavioural change was associated with right frontal hypoperfusionLevy et al. (2018)Regression; R 2 Not specifiedNot specified R 2 = =0.45 for self-regulation mask- Outcomes from measures of clinical judgement were more robust than patient-informant DS when correlating with brain structures.- Altered global insight correlated with left OFC and right rostral ACC in the whole cohort of patients (bvFTD, CBS and PPA).- Episodic memory functioning did not predict altered insight.Ichikawa et al. (2013)Two-tailed Fisher correlation p < 0.05N/A (areas of horns measured in mm2) p = 0.0016 for anterior horn; p < 0.0001 for inferior horn- Significant positive correlations between anosognosia scores and increase of anterior and inferior horns sizes (indexes of frontotemporal atrophy) in ALS, but especially ALS with FTLD.- Longitudinal increases of horn sizes were significantly more rapid in non-demented ALS patients compared with controls.- The anosognosia score was predominantly correlated with longitudinal enlargement of the inferior horn size (index of medial temporal lobes atrophy) in non-demented ALS patients.Hornberger et al.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…(2006)Ordinal regression; F and Bonferroni tests p < 0.005Not applicable (visual inspection) p < 0.001Loss of insight into behavioural change was associated with right frontal hypoperfusionLevy et al. (2018)Regression; R 2 Not specifiedNot specified R 2 = =0.45 for self-regulation mask- Outcomes from measures of clinical judgement were more robust than patient-informant DS when correlating with brain structures.- Altered global insight correlated with left OFC and right rostral ACC in the whole cohort of patients (bvFTD, CBS and PPA).- Episodic memory functioning did not predict altered insight.Ichikawa et al. (2013)Two-tailed Fisher correlation p < 0.05N/A (areas of horns measured in mm2) p = 0.0016 for anterior horn; p < 0.0001 for inferior horn- Significant positive correlations between anosognosia scores and increase of anterior and inferior horns sizes (indexes of frontotemporal atrophy) in ALS, but especially ALS with FTLD.- Longitudinal increases of horn sizes were significantly more rapid in non-demented ALS patients compared with controls.- The anosognosia score was predominantly correlated with longitudinal enlargement of the inferior horn size (index of medial temporal lobes atrophy) in non-demented ALS patients.Hornberger et al.…”
Section: Resultsmentioning
confidence: 98%
“…Among the 37 papers shortlisted for full reading, 22 were considered not pertinent since they did not make use of neuroimaging or focused on neurogenerative diseases other than FTD. 15 studies met the selection criteria of this systematic review (Amanzio et al., 2016; Bastin et al., 2012; Garcia-Cordero et al., 2016; Hornberger et al., 2014; Ichikawa et al., 2013; Levy et al., 2018; Massimo et al., 2013; McMurtray et al., 2006; Mendez and Shapira, 2005; Miller et al., 1997; Rosen et al., 2010; Ruby et al., 2007; Shany-Ur et al., 2014; Sollberger et al., 2014; Zamboni et al., 2010) (Tables 2 and 3).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a computed tomography study performed in ALS patients with FTD found that impaired cognitive self-awareness, as evaluated by one 8-item scale about motor and cognitive abilities, was associated with enlargement of the anterior and inferior horn sizes of the lateral ventricle, which was interpreted as reflecting MTL atrophy (Ichikawa et al, 2013). This single although interesting study calls for in-depth neuroimaging investigations on self-awareness in ALS.…”
Section: Unawareness Of Memory Deficits Hasmentioning
confidence: 93%